An Analysis of Gaps in Elementary School Students’ Mathematical Literacy in Solving Contextual Problems - Ety Mukhlesiyeni (PGMI IAIN Lhokseumawe, 2025)
This study aims to analyze the gaps in elementary school students’ mathematical literacy when solving contextual problems. Mathematical literacy is understood as students’ ability to formulate, apply, and interpret mathematics in various real-life contexts. However, learning practices in elementary schools are often still dominated by procedural and textbook-oriented approaches, resulting in a gap between expected competencies and students’ actual abilities. This study employed a qualitative descriptive approach with a case study design. Data were collected through contextual mathematical literacy tests, analysis of students’ written work, classroom observations, and semi-structured interviews with students and teachers. The results indicate that the most prominent gaps occur in (1) understanding contextual situations, (2) translating contexts into mathematical representations, (3) selecting appropriate problem-solving strategies, and (4) interpreting mathematical solutions back into real-life contexts. These gaps are influenced by limited exposure to contextual problems, teachers’ focus on procedural mastery, and students’ low confidence in reasoning and argumentation. The findings suggest that systematic efforts are needed to integrate contextual and meaningful learning into elementary mathematics instruction to strengthen students’ mathematical literacy.